Bimbingan Perkawinan sebagai Upaya Edukasi Kesiapan Rumah Tangga di KUA Pasar Minggu - Naila Nurfadillah; Ramadan Asa Kamal; Sugiharto Sugiharto (Universitas Pahlawan Tuanku Tambusai, 2026)
The high divorce rate in Indonesia indicates that the readiness of prospective brides and grooms to build a successful married life still needs to be improved. In response, the government, through the Office of Religious Affairs (KUA), organizes the Marriage Guidance Program (Bimbingan Perkawinan/Binwin) as a form of premarital education. This community service activity aimed to enhance participants’ understanding of married life, the rights and responsibilities of spouses, conflict management, and the establishment of a sakinah, mawaddah, wa rahmah family. The program was conducted at the KUA of Pasar Minggu District, South Jakarta, using interactive lectures, discussions, question-and-answer sessions, reflection, and evaluation through Google Forms. The materials covered family development, marriage regulations, and mental and emotional preparedness. The results showed that participants actively engaged in the program and demonstrated improved understanding of family roles, conflict resolution, work–family balance, and readiness for marital challenges. The program positively contributed to preparing prospective couples for harmonious family life and should continue to be developed through more participatory and innovative approaches.